Analysis Of Workshop Layout On The Application Of Occupational Health And Safety In Department Of Civil Engineering Education and Planning UNY Carpentry Workshop - Indah Wahyuni; Nanda Awalia Enggar Salsabila; Galeh Nur Indriatno Putra Pratama (Universitas Negeri Yogyakarta, 2024)
Background: The implementation of a workshop layout that is not following the 2010 ILO & IEA regulations can cause work accidents, hence the need for OHS implementation in woodworking workshops. The objectives of this research are: (1) to determine the suitability of the layout of the Woodworking Workshop of DPTSP UNY with the 2010 ILO & IEA regulations. (2) To determine the suitability of the K3 implementation of the woodworking workshop of DPTSP UNY with SNI 45001 2018.Methods: The research method used in this study is descriptive static with a percentage scale. This research was conducted at the Woodworking Workshop of DPTSP UNY with the research sample being lecturers, technicians, and students who were using the workshop. Data was collected using a questionnaire with a Guttman scale.Results: The study yielded the following data: (1) There is conformity between the layout of the Woodworking Workshop and the ILO & IEA regulations with an average of 78%. (2) There is conformity of K3 in the woodworking workshop with SNI 45001 with an average of 90%.Conclusion: The suitability of the layout of the woodworking workshop can facilitate the movement of woodwork with the availability of tools that are quite complete, and the layout of the equipment makes it easy for students to find tools, besides that the storage and maintenance of tools is very well maintained. The suitability of K3 in the woodworking workshop provides a high guarantee of safety if it is supported by the discipline of using the correct work procedures and adherence to procedures. In addition, the room with K3 standard criteria to create a safe, comfortable, and healthy environment in carrying out practical activities.